Effects of chronic insomnia disorder to third-year dentistry students GPA: Efek gangguan insomnia kronik terhadap indeks prestasi kumulatif mahasiswa tahun ketiga fakultas kedokteran gigi - Widyatma Adinda Jubhari; Aryadil Arsyad; Eri Hendra Jubhari; Edy Machmud (Makassar Dental Journal PDGI Makassar, 2021)
Introduction: Insomniadisorder suffered by many students, and may affects learning process, academic performance, and health. Besides that, learning process, memory disorder, and emotional health may influence academic performance, which is an important thing for their future. Aim: To know whether chronic insomnia disorder affect the Grade Point Average of third year students from faculty of dentistry. Method: This is an observational analytic research with cross-sectional method, was performed in Faculty of Dentistry Hasanuddin University in October 2017 by total sampling. The variables are chronic insomnia disorder, and academic performance. Insomnia is diagnosed by Insomnia Screening Questionnaire, and data pro-cessed by SPSS 24 (Saphiro-Wilk and T independent test). Result: The result shows that there is one outlier which has been excluded, while insomnia disorder prevalence is about 82.25% of 62 samples, chronic insomnia disorder is about 59.67% of 62 samples, and there is no difference between GPA of chronic insomnia group and non-insomnia group (p=0.343). Con-clusion: Chronic insomnia disorder doesn’t affect the GPA of third-year students from faculty of dentistry.